2011
DOI: 10.1007/s10903-011-9528-8
|View full text |Cite
|
Sign up to set email alerts
|

Building Knowledge About Health Services Utilization by Refugees

Abstract: The objective of this study was to compare the utilization of outpatient physician, emergency department and hospital services between refugees and the general population in Calgary, Alberta. Data was collected on 2,280 refugees from a refugee clinic in Calgary and matched with 9,120 non-refugees. Both groups were linked to Alberta Health and Wellness administrative data to assess health services utilization over 2 years. After adjusting for age, sex and medical conditions, refugees utilized general practition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 48 publications
1
28
0
1
Order By: Relevance
“…In our study population, the rate of utilization of medical services among refugees was significantly higher than that of the U.S. population which agrees with the results of a study among refugees in Canada by Kiss and colleagues (6). It is worth noting that the home countries of refugees in the above mentioned study differ from that of this study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study population, the rate of utilization of medical services among refugees was significantly higher than that of the U.S. population which agrees with the results of a study among refugees in Canada by Kiss and colleagues (6). It is worth noting that the home countries of refugees in the above mentioned study differ from that of this study.…”
Section: Discussionsupporting
confidence: 92%
“…Recent research shows that rates of healthcare utilization among refugees in the U.S. are higher than that of the general population, yet health disparities exist between the two groups (6). Language barriers, lack of insurance and problems with transportation are identified as reasons for these disparities.…”
Section: Introductionmentioning
confidence: 99%
“…3 Refugees have statistically significantly higher rates of treatable and preventable diseases compared to the general Canadian population. [1][2][3]13 Refugees are susceptible to vaccine preventable diseases because of under-immunization in their home country, waning immunity from previous immunizations, or both. 3 The most common vaccine-preventable illnesses afflicting refugees are tetanus, measles, mumps, rubella, varicella, and hepatitis B.…”
Section: Refugees Have Poorer Healthmentioning
confidence: 99%
“…Resettlement services offered at the Margaret Chisholm Resettlement Centre provide 10 weeks of accommodation, immediate health services, and links to community services for government-sponsored refugees. New arrivals are diagnosed and treated for infectious and parasitic diseases such as bilharzia, giardia, malaria, post-primary tuberculosis, filarial and fungal infections, hepatitis B, and acquired immune deficiency syndrome/human immunodeficiency virus 4. Malnutrition and micro-nutrient deficiencies, notably of vitamin A, C, D, niacin, and iron, often accompany these diseases 59.…”
Section: Introductionmentioning
confidence: 99%
“…Anecdotal reports indicated that Sudanese babies were presenting at the local children’s hospital with neonatal rickets, a preventable condition attributable to maternal vitamin D deficiency 9. Although known deficiencies can be corrected by vitamin supplementation, health care workers suggested that this was an unfamiliar practice for Sudanese people, even if supplements were provided 4. These nutritional concerns may be indicative of greater issues faced by Sudanese refugees as they adapt to a new culture, and support the need to further explore how nutrient deficiencies can be treated in a culturally appropriate manner.…”
Section: Introductionmentioning
confidence: 99%